Akurasi empati pria lebih tinggi dari pada wanita: Persepsi Love Language pada Pasangan Berpacaran: Persepsi Love Language pada pasangan berpacaran - Klaudia Cempaka; Cornelius Widyatmoko (Merpsy Journal, 2026)
This study aims to examine differences in the accuracy of perceptions of dating partners’ love language styles based on gender. Given that divorce rates remain high and continue to rise, accurate perceptions of a partner’s love language may serve as a buffer against marital dissolution. It was hypothesized that there would be differences in perception accuracy between men and women, with women having greater perception accuracy regarding their partners’ love language styles compared to men. A quantitative correlational research design was employed to address the research question[MP1] . The participants consisted of 140 heterosexual dating couples aged 18 to 25 years. Data were collected used the Five Love Languages Scale as the main questionnaire, with slight linguistic adjustments made to measure participants’ perceptions of their partners’ love language styles. Contrary to findings from previous studies on empathy accuracy, the results showed that men demonstrated better perception accuracy regarding their partners’ love languages across all dimensions. These findings suggest that certain contexts in interpersonal relationships may enhance empathic accuracy in men.